MENINGKATKAN KEMAMPUAN BERBAHASA INDONESIA YANG BAIK BAGI SISWA IBTIDAIYAH (MI) MELALUI MEDIA PEMBELAJARAN MONOSA (MONOPOLI BAHASA) - ., Syarifuddin (Balai Diklat Keagamaan Surabaya, 2018)
This study aims to describe the development of children’s mediaMonosa independence based on learning Indonesian at MadrasahIbtidaiyah (MI). This study used a qualitative approach with disriptifresearch methods and using R & D procedures. Based on the resultsof the initial needs assessment obtained results expected media ismedia that is not only disposable and made of material that iswaterproof , medium-sized and can be placed on the table. Learningmedia containing material that diverses and covers all aspects oflanguage skills. Media with images that vary according to the materialfor Indonesian elementary school in fourth grade. Based on thevalidation results showed that the learning media Monosa fit foruse. It can be used by learners, learning media can also create anatmosphere of fun and do not saturate because the learning is donewhile playing .